Faktor - Faktor yang Mempengaruhi Niat Penggunaan Paylater Dengan Literasi Keuangan Sebagai Variabel Moderasi - Diah Larasati; Khoirul Fuad (Worksheet : Jurnal Akuntansi, 2026)
The increasing presence of financial technology in everyday life has influenced how generation Z students manage their finances, particulary through the growing use of paylater services, which raises concern about financial responsibility. This study aims to examine the factors influencing students intention to use paylater among university students in Semarang. The analysis is based on the Theory of Planned Behavior (TPB), including attitude, subjective norms, perceived behavioral control, and personal financial accountability, with financial literacy as a moderating variable. A quantitative approach was applied using a survey of 160 students, and the data were analyzed using PLS-SEM with SmartPLS version 4. The results indicate that attitude and subjective norms have a significant positive effect on intention, while perceived behavioral control and financial accountability do not show significants effects. Financial literacy also does not significantly moderate the relationships examined. These findings imply that students decisions are more influenced by personal perceptions and social pressures than by financial considerations, highlighting the importance of strengthening practical financial literacy programs to encourage more responsible use of digital credit services among young users.